Studi Analisis Celah Keamanan Website Spin Laboratorium Kalibrasi Menggunakan Metode Pemindaian Owasp Zap, Burp Suite, Dan Nessus - Rodiansyah, Hamdan; Muttaqin, Helmy Faisal (Syntax Corporation, 2025)
This research analyzes security vulnerabilities on the SPIN Laboratory Calibration website using three scanning tools: OWASP ZAP, Burp Suite, and Nessus. The scans aim to detect vulnerabilities aligned with the OWASP Top 10 and other vulnerabilities such as SQL Injection and XSS. The results show that each tool has its strengths in detecting specific vulnerabilities, with OWASP ZAP focusing on configuration issues, Burp Suite being effective in manual attacks, and Nessus providing a more comprehensive analysis. Based on these findings, the study offers mitigation recommendations to enhance website security.